UNESCO Global Report 2022 - United Nations Educational, Scientific; Cultural Organization (United Nations, 2022)
The Global Report series monitors the implementation of the 2005 Convention on the Protection and Promotion of the Diversity of Cultural Expressions, as well as progress towards achieving the United Nations 2030 Agenda for Sustainable Development, within and with the cultural and creative sectors. Its 2022 edition revolves around two major questions: What is the state of the cultural and creative sectors? What policy changes to promote sustainable, human rights-based systems of governance for culture and equitable access to cultural opportunities and resources have resulted from stakeholders’ implementation and ownership of the Convention? In line with the 2015 and 2018 editions, this third edition of the Report presents the latest policy developments to support creativity and sheds light on current and future challenges in areas such as the digital environment, media diversity, sustainable development, mobility of artists and cultural professionals, gender equality and artistic freedom.